1994
DOI: 10.1007/s001250050190
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms underlying the insulinostatic effect of peptide YY in mouse pancreatic islets

Abstract: Summary Peptide YY is an insulinostatic peptide which is released into the circulation from the intestinal mucosa upon food intake. Peptide YY is also co-stored with glucagon in the secretory granules of the pancreatic alpha cells. We examined the mechanisms underlying the insulinostatic effect of peptide YY in isolated mouse pancreatic islets. We found that peptide YY (0.1 nmol/1-1 ~tmol/1) inhibited glucose (11.1 mmol/1)-stimulated insulin secretion from incubated isolated islets, with a maximal inhibition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Intravenously administe no eVect on basal plasma insulin levels, but cose-stimulated insulin secretion in mice (B 1989;Szecowka et al, 1983). In vitro studi that PYY dose-dependently inhibits gluco but not basal insulin secretion (Karlsson 1996;Nieuwenhuizen et al, 1994). Studies u islets isolated from rats suggest that this is a of PYY on islets (Bertrand et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenously administe no eVect on basal plasma insulin levels, but cose-stimulated insulin secretion in mice (B 1989;Szecowka et al, 1983). In vitro studi that PYY dose-dependently inhibits gluco but not basal insulin secretion (Karlsson 1996;Nieuwenhuizen et al, 1994). Studies u islets isolated from rats suggest that this is a of PYY on islets (Bertrand et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenously administered PYY inhibits glucose-stimulated insulin secretion as well as carbachol-and arginine-induced glucagon secretion in mice [12] and [45]. In vitro studies also demonstrate that PYY dose-dependently inhibits glucose-stimulated but not basal insulin secretion [38]. This is supported by work on isolated mouse islets where PYY antiserum potentiates glucoseinduced insulin secretion in culture [25].…”
Section: Effect Of Pyy1-36 On Glucose Homeostasismentioning
confidence: 96%
“…One study has suggested that PYY inhibits insulin secretion by inhibiting the accumulation and action of cyclic AMP [38]. However, as adenylate cyclase inhibition is a feature of all Y receptor subtypes, it was not determined which Y receptor subtype was involved in the PYY-mediated inhibition of insulin secretion [38].…”
Section: Mechanisms For Pyy-mediated Inhibition Of Insulin Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence reveals an emerging role of PYY involved in glucose homeostasis. In vitro study has showed that PYY inhibits glucose stimulated insulin secretion from the isolated islets by inhibiting the accumulation and action of cAMP [56]. In vivo evidence also suggests that deiciency of PYY in mice signiicantly increases body weight and fat mass.…”
Section: Peptide Yymentioning
confidence: 99%